2011
DOI: 10.1021/bi2001938
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Substrate Specificity Determinants Recognized by the Active Site of C-Terminal Src Kinase-Homologous Kinase (CHK) and Identification of β-Synuclein as a Potential CHK Physiological Substrate

Abstract: C-terminal Src kinase-homologous kinase (CHK) exerts its tumor suppressor function by phosphorylating the C-terminal regulatory tyrosine of the Src-family kinases (SFKs). The phosphorylation suppresses their activity and oncogenic action. In addition to phosphorylating SFKs, CHK also performs non-SFK related functions by phosphorylating other cellular protein substrates. To define these non-SFK related functions of CHK, we used the `kinase substrate tracking and elucidation' method to search for its potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…After reduction and alkylation, gel pieces from each protein band were washed twice with 200 μL of a 1:1 (v/v) 100 mM NH 4 HCO 3 /acetonitrile mixture for 15 min, followed by dehydration with 200 μL of 100% acetonitrile, and air-dried for 5 min. Dry gel pieces were rehydrated with 40 μL of 50 mM NH 4 HCO 3 containing 250 ng of trypsin (Sigma) and then incubated at 37°C overnight [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…After reduction and alkylation, gel pieces from each protein band were washed twice with 200 μL of a 1:1 (v/v) 100 mM NH 4 HCO 3 /acetonitrile mixture for 15 min, followed by dehydration with 200 μL of 100% acetonitrile, and air-dried for 5 min. Dry gel pieces were rehydrated with 40 μL of 50 mM NH 4 HCO 3 containing 250 ng of trypsin (Sigma) and then incubated at 37°C overnight [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…It is reasonable to hypothesize that phosphorylation of these tyrosine residues could affect the propensity of bS to aggregate, since aS aggregation is negatively regulated by phosphorylation of the corresponding tyrosine residues (i.e., Y125, Y133 and Y136) in aS [44,45]. Indeed, it was recently shown that Y127 in bS is preferentially phosphorylated by the C-terminal Src kinase-homologous kinase (CHK) [46]. Furthermore, it should be noted that bS is a major o-glycosylated protein in the presynaptic regions of the rodent brain, together with UCH-L1 (PARK5) and collapsin response mediator protein-2 [47].…”
Section: Does Altered Bs Function Initiate a Neurotoxic Cascade In A-mentioning
confidence: 99%
“…In addition, peptides that are derived from authentic protein substrates of kinases can lack key determinants of specificity and thus make inefficient substrates, as in the case of the phosphorylation of the C-terminal tail of Src family kinases by their upstream regulators CSK and CHK. 21 …”
Section: Introductionmentioning
confidence: 99%